Real-time machine controller verification and simulation using control signals emulation - Hussein, Mohamed (Institute of Electrical and Electronics Engineers, 2009)
The research study explores different types of controller simulation and verification methods and proposes a new method which employs the use of a control signals emulator. The research study has formulated a novel technique for emulating quadrature encoder signals to provide virtual closed loop control of servomotors. The deployment of a control signal emulator technique makes the system unique and removes its dependency on proprietary hardware or software. Enabling the real-time data from the signal emulation environment eases the task of realising a real-time machine simulator.